Too many cooks in the kitchen? The division of financing in World Bank projects and project performance - Matthew S. Winters (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The total funding envelope for World Bank projects is often divided among various state and non-state actors, each of which can have competing ideas about or interests in the project. How does the division of financing relate to overall project effectiveness? I argue that too many funding streams in a project can reduce project effectiveness by creating delays, increasing transaction costs, and blurring lines of accountability. I combine original data on the number and concentration of financial collaborators in World Bank projects with the World Bank's ratings of project performance, looking at within-country variation across projects to explore whether there is evidence of reduced aid effectiveness in projects with more participants. The results suggest that projects with significant co-financing receive somewhat worse project ratings.
Keywords: F33; F34; F35; O12; O19; 330; aid effectiveness; co-financing; foreign aid; World Bank